2019
DOI: 10.1002/mar.21195
|View full text |Cite
|
Sign up to set email alerts
|

“Autonomous, yet Connected”: An esthetic principle explaining our appreciation of product designs

Abstract: Esthetic principles describe the levels or combination of design dimensions that are esthetically appreciated. Current principles focus on dimensions connected to product design itself (e.g., unity and variety) or dimensions that refer to a product design's relationship to other product designs (e.g., typicality and novelty). However, product design also has a social significance—they help consumers shape their identity—and this social dimension has hitherto been overlooked in research on esthetic appreciation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 66 publications
0
10
1
Order By: Relevance
“…Moreover, the literature suggests that nostalgia serves to strengthen social connectedness (Loh et al, 2021;Seehusen et al, 2013;Wildschut et al, 2006). In general, people have a strong desire to have and maintain lasting interpersonal relationships and the need to belong is one of the main motives of human behavior (Baumeister & Leary, 1995;Blijlevens & Hekkert, 2019;…”
Section: Nostalgic Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the literature suggests that nostalgia serves to strengthen social connectedness (Loh et al, 2021;Seehusen et al, 2013;Wildschut et al, 2006). In general, people have a strong desire to have and maintain lasting interpersonal relationships and the need to belong is one of the main motives of human behavior (Baumeister & Leary, 1995;Blijlevens & Hekkert, 2019;…”
Section: Nostalgic Consumptionmentioning
confidence: 99%
“…Moreover, the literature suggests that nostalgia serves to strengthen social connectedness (Loh et al, 2021; Seehusen et al, 2013; Wildschut et al, 2006). In general, people have a strong desire to have and maintain lasting interpersonal relationships and the need to belong is one of the main motives of human behavior (Baumeister & Leary, 1995; Blijlevens & Hekkert, 2019; Stokburger‐Sauer, 2010). Under threatening situations, people often count on social support for intimacy and protection (Cohen & Wills, 1985), which also depends on their attachment‐related avoidance (Bowlby, 1969).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Furthermore, a product metaphor associates a source with a target product, whereby the source and target share the same meanings or physical similarities (Cheng et al, 2019; Hekkert, & Cila, 2015; Van Rompay, 2008). Integrating a metaphor into the product design distinguishes it from other typical designs that are already familiar to the consumer (Blijlevens & Hekkert, 2019). Cheng et al (2019) showed that an underlying metaphor can be simultaneously used to increase the understanding of product innovation.…”
Section: Conceptual Background and Hypothesis Developmentmentioning
confidence: 99%
“…Form is the appearance (i.e., how a product looks) and function reflects capabilities (i.e., how a product works). Form is perhaps most often associated with design, as it is the outward appearance that generates initial impressions of a product in both direct, material ways and indirect, symbolic ways (Blijlevens & Hekkert, 2019; Bloch, 1995, 2011). Function is less immediately obvious because it reflects a product's workings, features, and problem‐solving capabilities (M. Luchs & Swan, 2011; Ulrich & Eppinger, 1995).…”
Section: Literature Backgroundmentioning
confidence: 99%
“…Moreover, the imitation literature has traditionally examined the degree of imitativeness (Lee & Zhou, 2012; F. Wang & Chen, 2020) while overlooking other important product design factors, leaving a recent call for more studies of “ what is imitated” (van Horen & Pieters, 2012, p. 253, italics are original) unanswered. A new product is a bundle of functions, assumes an esthetic form (Blijevens & Hekkert, 2019; Hagtvedt & Patrick, 2014; Ulrich & Eppinger, 1995), and is designed to satisfy consumers' hedonic or utilitarian needs (Amatulli, De Angelis, & Donato, 2020; Batra & Ahtola, 1991), so an imitative new product could be imitative in either its form, function, or both, and could be hedonic or utilitarian. As such, it is imperative to examine the roles of important product design characteristics such as imitation locus, imitation scope, and product hedonism as factors that affect the efficacy of face consciousness on consumer purchases of imitative new products.…”
Section: Introductionmentioning
confidence: 99%